Study of acute intestinal obstruction management and its outcome - M., Valarmathi (International Surgery Journal, 2021)
Background: Acute intestinal blockage (AIO) is a common abdominal emergency with a high morbidity and mortality rate. Early blockage diagnosis, skilled operative management, correct technique during surgery and intense postoperative therapy yield superior results. The aim was to study the aetiology, clinical presentation, therapy and outcomes of patients with IO who presented in the emergency department. Methods: This prospective study was conducted at the general surgery department from June 2019 to May 2021. The study comprised 60 patients with IO who presented to the OPD or emergency room and the data was analysed. Results: Among 60 patients with IO, peak incidence was observed in patients above 50 years of age, predominantly among males. Abdominal pain turned out to be the most common symptom of IO in our patients. Patients obstructed in the small intestine were found to be predominant. Post-operative adhesions were the most common cause of IO. Conclusions: Early diagnosis, proper preoperative hydration, fast investigations, and early operational intervention were found to increase survival in patients with intestinal obstruction in the current study.